A study on urban morphology using GIS & remote sensing technique - Mohd Nor, Marina; Hj. Mohd. Noor, Norzailawati (2014)
Urban morphology is the study of the form of human settlements and the process of their formation and transformation. It is an approach in designing urban form that considers both physical and spatial components of the urban structure. Penang was awarded as Heritage City by UNSECO in July 2008. Penang is well known for its heritage character especially in the city of Georgetown with more than 200 years of urban history. Therefore, the study has conducted in Georgetown, Penang in order to identify the evolution of urban morphology and the expansion of development in terms of land use activity. This paper attempts to review a literature that is related to urban morphology in the context of using GIS and remote sensing techniques. These techniques are most widely used and the development in both technology applications has led to significant improvement in capability for decision making process. Therefore, it will help to investigate the past and present patterns and trends of urban growth in Georgetown, Penang. Thus, this finding would contribute to understand the interrelation between urban morphology study and the applications of GIS and remote sensing and its influence on creating sustainable and resilience of metropolitan area, city, town or even village.